Patient Expectation in China: Exploring Patient Satisfaction in Online and Offline Patient–Provider Communication - Cao, Bolin; Wang, Dongya; Wang, Yifan; Hall, Brian J. (Frontiers in Psychology, 2022)
Introduction: Online patient-provider communication (OPPC) has become an alternative approach to seek medical advice and contact health professionals. However, its penetration rate remains low, and the underlying mechanisms of patient satisfaction with OPPC are underexamined. This study investigates the role of patient expectancy and the expectancy violation of patient-centered communication (PCC) in patient satisfaction in emerging OPPC scenarios by integrating the concepts of PCC and expectancy violation theory (EVT). Method: An online survey was conducted in October 2019 among Chinese respondents who experienced OPPC and offline medical services. Results: The 471 qualified participants reported high satisfaction with OPPC (mean [M] = 3.63, standard deviation [SD] = 0.81). However, patient satisfaction with OPPC was lower than that in offline medical encounters (M = 3.75, SD = 0.80), and patients suffered a higher expectancy violation of PCC in OPPC scenarios (M = 0.45, SD = 0.76) than in offline medical encounters (M = 0.27, SD = 0.69). Nevertheless, patients’ satisfaction with OPPC significantly increased as the frequency of OPPC usage increased (β = 0.209, p < 0.001). This positive relationship was partially mediated by the decrease in the expectancy violation of PCC in OPPC scenarios. Discussion: The study can contribute to increasing the adoption of OPPC and reducing the burden of offline medical resources.